Analysis of Medical Record Document Management Based on The Assessment Elements of MRMIK 3 LAM-KPRS at Mutiara Bunda Mother and Child Hospital - Dewi Oktavia; Sayati Mandia (Ficco Public Health Journal, 2025)
Background: Accreditation is recognition given to hospitals for their efforts to continuously improve the quality of service. One of the accreditation institutions for hospital quality and patient safety is LAM-KPRS. The implementation of MRMIK 3 focuses on document management and hospital policies. RSIA Bunda Padang has specific needs in implementing this system, particularly in recording patient data related to pregnancy, childbirth, and neonatal care, thus requiring a system capable of supporting real-time data access. The aim of the study was to determine the results of the analysis of medical record document management based on the MRMIK 3 LAM-KPRS Assessment Elements at Mutiara Bunda Mother And Child Hospital. Methods: This study used a qualitative design and was conducted from March to April 2025. The sampling method used purposive sampling with a total of 3 people. The data collection technique used observation with research instruments, namely checklists based on the MRMIK3 LAM-KPRS accreditation assessment and conducted in-depth interviews with informants. Data analysis was carried out in three main steps: data reduction, data presentation, and drawing conclusions. Results: The results of the study showed that the hospital had implemented document management according to the criteria with a partially met assessment, had and implemented a uniform format for similar documents with a met assessment, and had documents with a partially met assessment. Conclusion: from the three assessment indicators, some were fulfilled and some were partially fulfilled.